Impact of the demand for ‘proxy assent’ on recruitment to a randomised controlled trial of vaccination testing in care homes - Whelan, Paul James (Journal of medical ethics, 2013)
Legal frameworks are in place to protect those who lack the capacity to consent to research, such as the Mental Capacity Act in the UK. Assent is sought instead from a proxy, usually a relative. However, the same legislation may, perversely, affect the welfare of those who lack capacity and of others by hindering the process of recruitment into otherwise potentially beneficial research. In addition, the onus of responsibility is moved from those who know most about the study (ie, the scientific community) to those who know less (the proxies). In this paper, we describe the characteristics of a sample at different stages of the recruitment process of an influenza vaccine-based randomised control trial in elderly care home residents (the FEVER study). 62% (602/968) of potential subjects lacked capacity but only 29% (80/277) of those actually randomised. Older age, being female and living in an Elderly Mentally Ill care home were the only variables associated with lacking capacity. Considering this was a study based in a care home setting where the prevalence of dementia approximates 80%, the trial, like many others, was thus significantly biased. We believe that difficulties seeking proxy assent contributed significantly to this problem. Further thought should be given to how assent to enter research for those who lack capacity should be provided, and we suggest avenues for further discussion such as independent risk/benefit expert panels.